Botryllus stewartensis Brewin 1958 - Kott, Patricia (Zenodo, 2006)
Botryllus stewartensis Brewin, 1958 (Figure 10H) Botryllus stewartensis Brewin 1958, p 444; Kott 1990b, p 286 and synonymy. Distribution Previously recorded (see Kott 1990b): Western Australia (Albany); South Australia (Spencer and St Vincent Gulfs); Victoria (Ninety Mile Beach, Port Phillip Bay); New South Wales (Port Kembla, Port Stephens, Port Hacking); Queensland (Moreton Bay); New Zealand (South I. and Stewart I.). New record: South Australia (Edithburgh, 3–4 m, SAM E3289). Description The newly recorded colonies are squat, sandy lobes (to 1 cm high and 1 cm diameter) on a basal mat. Each lobe contains a single common cloacal system consisting of a circle of zooids around a central common cloacal aperture. The zooids open from the upper flat surface, which is slightly depressed in the preserved colonies. The test is delicate and soft, and covered with sand, although sand is not present internally. Zooids are as previously described with about 10 rows of about 15 stigmata and three delicate internal longitudinal vessels running the length of the branchial sac. The ventral internal longitudinal vessel is close to the endostyle. A small, curved gastric caecum is at the pyloric end of the stomach. Remarks The species shows little variation, despite its wide geographic range. The height of the flattopped colony lobes does vary, sometimes reaching 3.5 cm but their diameter is less variable, reaching only 1.5 cm. The presence of a circular zooid system and the sandy external covering are characteristic. Other temperate species have a similar recorded range, across the southern Australian coast from Albany and up the eastern coast to Moreton Bay. However, the occurrence of the species in the South Island and Stewart I. (New Zealand) suggest a possible sub-Antarctic affinity. Sandy species of the subfamily Botryllinae are unusual. Botrylloides saccus Kott, 2003 from Kangaroo I. has similar circular systems but small almost spherical colony lobes on short, thin stalks. Botryllus purpureus (Oka, 1932) has encrusting ...